Bit Error Rate (BER) Performance of Hybrid Beamforming for mmWave in 5G Massive MIMO Systems - Ahmad Ridauddin, Shafiah Aienn; Katiran, Norshidah (Evolution in Electrical and Electronic Engineering, 2026)
mmWave massive MIMO is a promising technology for enhancing overall network performance in 5G and beyond 5G. Beamforming is employed in massive MIMO systems to spatially direct the transmitted signal toward intended users while suppressing interference. While analogue beamforming (ABF) offers a simpler signal implementation, its performance is inferior to that of fully digital beamforming (DBF). To overcome these issues, hybrid beamforming (HBF) is proposed to balance performance and hardware efficiency by combining ABF and DBF. The objective of the project is to develop a 5G mmWave massive MIMO system with hybrid beamforming that employs Joint Spatial Division Multiplexing with Per-Group Processing (JSDM-PGP). Next, the investigation of the effects of the number of transmit antennas in the multi-user system on overall performance. Finally, the system performance is measured in terms of bit error rate (BER). Results obtained using the JSDM-PGP technique indicate that increasing the number of transmit antennas from 128 to 512 leads to a noticeable reduction of 19.51% for BER. In addition, the proposed JSDM-PGP scheme is benchmarked against JSDM-JGP to assess the relative improvements in BER under different transmit antenna configurations. For future work, this study can be extended to more realistic mmWave communication scenarios by considering user mobility, dynamic blockage, imperfect CSI, adaptive bandwidth and power allocation, to further evaluate the robustness and practical suitability of JSDM-PGP and JSDM-JGP in next-generation wireless networks.